Issues with the Swedish e-prescribing system – An analysis of health information technology-related incident reports using an existing classification system. (October 2022) - Rahman Jabin, Md Shafiqur; Hammar, Tora
Objective: To identify issues with the Swedish e-prescribing system and devise a set of recommendations to overcome the identified challenges. Methods: A number of health information technology-related incidents were collected retrospectively from various sources using purposive and snowball sampling. A search term containing five keywords was used to identify the electronic prescription-related incidents. The identified incidents ( n  = 24) were subjected to an existing framework, i.e., the Health Information Technology Classification System. Special attention was paid to the software-related issues, which were analysed using thematic analysis. Results: Several types of software-related issues ( n  = 22) were identified: system configuration, interface with other software systems or components, software functionality, data storage and backup, record migration, software not accessible, and network/server down or slow. Both human and technical factors contributed to these incidents, including prescriptions not cancelled actively, drug handling errors, software programming errors, and system updates/upgrades. These software problems led to various consequences, such as incidents affecting multiple patients' care management, delays in patient care, and risks of serious deterioration of health. Several temporary initiatives or administrative adjustments, for instance, cover letters to patients and local strategies, were used to overcome some of these challenges. Conclusions: This study provides insights into the challenges related to the e-prescribing system, contributing factors, consequences, and actions taken to mitigate those risks. Therefore, healthcare organisations using the e-prescribing system should adopt the provided recommendations to minimise the risks of design and developmental challenges, implementation and use-related issues, and the problems related to monitoring, evaluation, and optimisation.